Mechanism of action of icaritin on uterine corpus endometrial carcinoma based on network pharmacology and experimental evaluation - Jin, Yan-Bin; Liang, Xiao-Chen; Cai, Jun-Hong; Wang, Kang; Wang, Chen-Yang; Wang, Wen-Hua; Chen, Xiu-Li; Bao, Shan (Frontiers in Oncology, 2023)
Background: Uterine corpus endometrial carcinoma (UCEC) belongs to a group of epithelial malignant tumors. Icaritin is the main active compound of Epimedii Folium. Icaritin has been utilized to induce UCEC cells to death.We wished to identify potential targets for icaritin in the treatment of UCEC, as well as to provide a groundwork for future studies into its pharmacologic mechanism of action.Network pharmacology was employed to conduct investigations on icaritin. Target proteins were chosen from the components of icaritin for UCEC treatment. A protein-protein interaction (PPI) network was established using overlapping genes. Analyses of enrichment of function and signaling pathways were undertaken using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, respectively, to select "hub genes".Finally, experiments were carried out to ascertain the effect of icaritin on endometrial cancer (HEC-1-A) cells.We demonstrated that icaritin has bioactive components and putative targets that are therapeutically important. Icaritin treatment induced sustained activation of the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt pathway) and inhibited growth of HEC-1-A cells.Conclusions: Our data provide a rationale for preclinical and clinical evaluations of icaritin for UCEC therapy.